2022
DOI: 10.33087/jiubj.v22i3.3057
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan dengan Perilaku Kerja Inovatif sebagai Variabel Mediasi pada Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Muaro Jambi

Abstract: This study aims to determine the effect of transformational leadership and work motivation on employee performance with innovative work behavior as a mediating variable for employees of the Investment and One Stop Service Office of Muaro Jambi Regency. The research method used is a quantitative method, and the data collection technique uses a questionnaire with a Likert scale. The population is 47 employees of the State Civil Apparatus and Honorary Employees of the Investment and One Stop Service Office of Mua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…The mediating effect of innovative work behaviour on the relationship between transformational leadership style and employee performance Based on the test results, innovative work behaviour has not been able to mediate the effect of transformational Leadership on employee performance. These results differ from research conducted byFathiyah (2022) which concluded that transformational Leadership influences employee performance mediated by innovative work behaviour among employees of the Investment and One-Stop Service Office, Muaro Jambi Regency. The results of this study also contradict the results of research conducted byPertiwi (2019), which shows that transformational Leadership has a positive and significant effect on employee performance with innovative work behaviour as an intervening variable.…”
contrasting
confidence: 99%
“…The mediating effect of innovative work behaviour on the relationship between transformational leadership style and employee performance Based on the test results, innovative work behaviour has not been able to mediate the effect of transformational Leadership on employee performance. These results differ from research conducted byFathiyah (2022) which concluded that transformational Leadership influences employee performance mediated by innovative work behaviour among employees of the Investment and One-Stop Service Office, Muaro Jambi Regency. The results of this study also contradict the results of research conducted byPertiwi (2019), which shows that transformational Leadership has a positive and significant effect on employee performance with innovative work behaviour as an intervening variable.…”
contrasting
confidence: 99%
“…Then (Alviani & Nuvriasari, 2022) added that the higher the creative work behavior of an employee's work, the higher the quality of employee performance. The results of this study support (Fathiyah et al, 2022), who found that innovative work behavior can mediate the relationship between transformational leadership and employee performance.…”
Section: Transformational Leadership Affects Employee Performance Med...supporting
confidence: 87%
“…For example, they may feel joy, interest, or a sense of personal achievement when engaging in a specific activity, even without external rewards or praise from others (Fathiyah, et al, 2022). This concept differs from extrinsic motivation, where individuals perform an action because there are expected external rewards or consequences.…”
Section: Intrinsic Motivationmentioning
confidence: 99%